Positive end-expiratory pressure in acute respiratory distress syndrome: should the 'open lung strategy' be replaced by a 'protective lung strategy'? - Rouby, Jean-Jacques; Ferrari, Fabio [UNESP]; Bouhemad, Belaid; Lu, Qin (Biomed Central Ltd., 2007)
In patients with acute respiratory distress syndrome, positive end-expiratory pressure is associated with alveolar recruitment and lung hyperinflation despite the administration of a low tidal volume. The best positive end-expiratory pressure should correspond to the best compromise between recruitment and distension, a condition that coincides with the best respiratory elastance.